Application of the EAEU law by national courts and development of judicial dialogue - E. B. Diyachenko (Правоприменение, 2022)
The subject. This article examines the dialogue between the EAEU Court and national courts, on the one hand, as the application by national courts of the court of the integration organization, on the other hand, – as a recourse by the supranational court to the legal constructions that have been developed in the case law of the Member States’ courts.The purpose of the article is to confirm or disprove hypothesis that judicial dialogue between the court of the integration association and the courts of its Member States is the key to the effective application of supranational law.The methodological basis of the research is the doctrine of EU law, as well as the practice of Court of Justice of the European Union. The formal legal interpretation of the EAEU Court decisions and decisions of national Supreme Courts is also used.The main results, scope of application. One of the characteristics that differentiates the law of an integration organization from universal international law is its active application not only by the judicial body of such an organization, but also by the national courts. The plurality of actors in charge of the application of the law raises the question which of them have the authority of interpreting the integration law and the modalities of such an interpretation. One of the instruments that could help overcome the lack of uniformity of approaches regarding the interpretation and application of supranational law by the courts of several member states is the preliminary reference procedure. In the absence of such a procedure the burden of interpretation of supranational law rests on the national courts. Such a situation has arisen in the Eurasian Economic Union where the EAEU Court is empowered to interpret the law of the Union while settling disputes regarding the respect of EAEU law by its Member States, the challenge of the Eurasian Economic Commission's actions (failure to act) and decisions as well as delivering advisory opinions. The courts of the Member States, in turn, interpret the law of the EAEU in various fields of relations, including the ones where regulatory powers have been transferred to the supranational level. The analysis of national case law shows that in their application of EAEU law they premise their judgments on the principle of its primacy over national legislation.Conclusions. Judicial dialogue allows to prevent the non-uniform interpretation of the Union law by the court of the 5 Member States. It is a form of exchange of legal positions and concepts between the judicial bodies which, as a result, leads to a mutual enrichment of the legal orders by borrowing legal constructions and approaches.